The International Labour Organization and globalization: fundamental rights, decent work and social justice - Reynaud, Emmanuel (Geneva, 2018)
"This paper discusses how the ILO reacted to the challenges to its raison d’être posed by the end of the Cold War and the new globalization era. It shows that its continued relevance was attained in three main stages: the adoption of the 1998 Declaration, the development of the “decent work” concept and the adoption of the 2008 Declaration. The paper examines the Declaration on Fundamental Principles and Rights at Work, its adoption, its logic, achievements and limitations. It then discusses the definition and the promotion of the “decent work” concept, and its inclusion in the UN system and the international arena. Thereafter, it covers the 2008 Declaration on Social Justice for a Fair Globalization, the intricate process towards its adoption, its objectives, principles and potential. Finally, the paper shows how the ILO has reinforced the notion of “social justice” as a central aim of national and international policies."